Traits link drought resistance with herbivore defence and plant economics in semi‐arid grasslands: The central roles of phenology and leaf dry matter content - Blumenthal, Dana M.; Mueller, Kevin E.; Kray, Julie A.; Ocheltree, Troy W.; Augustine, David J.; Wilcox, Kevin R.; Cornelissen, Hans (The Journal of ecology, 2020)
Despite progress in trait‐based ecology, there is limited understanding of the plant traits that structure semi‐arid grasslands. In particular, it remains unclear how traits that enable plants to cope with water limitation are related to traits that influence other key functions such as herbivore defence and growth. The hypothesis that drought and herbivory exert convergent selection pressures is supported for morphological traits, but largely untested for structural, physiological and phenological traits. Drought and economic traits can also covary, but where and to what degree remains uncertain. Here we address these uncertainties in semi‐arid shortgrass steppe and mixedgrass prairie, the largest remaining grasslands in North America. Using a broad selection of traits for 37 of the most common plant species in each ecosystem, we ask whether traits that confer drought tolerance, avoidance and escape covary with herbivore resistance traits and economic traits. Results reveal that both drought tolerance and escape are coordinated with other functions, but in opposite fashion. Drought‐tolerant species (low leaf osmotic potential and high leaf dry matter content, LDMC) were also herbivore resistant (high leaf toughness and cellulose) and at the ‘slow’ end of the economic spectrum (low leaf nitrogen, leaf phosphorus and high stem density). Conversely, drought escape via early senescence was associated with lower drought tolerance, lower herbivore resistance and ‘fast’ economic traits. Drought avoidance, as indicated by thick leaves, may also be associated with lower drought tolerance (LDMC). Senescence date and LDMC appear to be key traits in these semi‐arid grasslands, differentiating species along multiple axes of function. Synthesis. Covariation between drought, herbivory and economic traits means that, of the many potential trait combinations, few actually exist within these grasslands. Consequently, changes in land management and climate should have predictable effects on drought resistance, forage quality and productivity in the western Great Plains. Trait covariation in two semi‐arid grasslands demonstrates that plant strategies for coping with water limitation are closely tied to both herbivore resistance and plant economics. Drought‐tolerant species have tough, high‐cellulose leaves and lie at the slow end of the economic spectrum. Drought‐escaping species have contrasting characteristics. Management and climate should therefore have predictable effects on forage quality and drought resistance.